2020
DOI: 10.3390/cancers12041036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CCL21/CCR7 Chemokine Axis in Breast Cancer Progression

Abstract: Breast cancer is a leading cause of cancer-related deaths worldwide, predominantly caused by metastasis. It is generally accepted that the pattern of breast cancer metastasis is largely determined by the interaction between the chemokine receptors on cancer cells and the chemokines expressed at the sites of metastatic disease. Chemokine receptors belong to the G-protein-coupled receptors (GPCRs) family that appear to be implicated in inflammatory diseases, tumor growth and metastasis. One of its members, C-C C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 142 publications
(168 reference statements)
2
53
0
Order By: Relevance
“…Moreover, CCR7 induction in EBV-infected cells was recurrently proposed to enable homing of lymphoid cells to secondary lymphoid tissue, where the virus in turn propagates infection or establishes latency, thereby driving lymphomagenesis 52 . It is further tempting to speculate on a potential role of oncogenic CCR7 mutations in EBV + DLBCL (NOS), prompting cellular proliferation and migration upon the binding of the cognate chemokine receptors, as was recently shown in breast cancer and other solid tumors 53 . Of note, we describe oncogenic mutations in DAPK1 as an exclusive feature of EBV + DLBCL (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CCR7 induction in EBV-infected cells was recurrently proposed to enable homing of lymphoid cells to secondary lymphoid tissue, where the virus in turn propagates infection or establishes latency, thereby driving lymphomagenesis 52 . It is further tempting to speculate on a potential role of oncogenic CCR7 mutations in EBV + DLBCL (NOS), prompting cellular proliferation and migration upon the binding of the cognate chemokine receptors, as was recently shown in breast cancer and other solid tumors 53 . Of note, we describe oncogenic mutations in DAPK1 as an exclusive feature of EBV + DLBCL (NOS).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have proved that these signaling pathways above played key roles in tumor proliferation, migration, invasion, and metastasis. 52 , 58 And they could also affect treatment effect and clinical outcome by mediating the migration and localization of immune cells, the immune responses, and the balance between immunity and tolerance. 59–61 These data suggested that CC chemokine receptors could be used as potential immunotherapy targets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that cancer cells can upregulate CCR7 expression and hijack its normal functions, enabling them to migrate along the gradient of CCL19 and CCL21 towards the lymph node and colonise them as a first step towards metastasis. In support of this hypothesis, CCR7 up regulation and correlation to lymph node (LN) metastasis is demonstrated in a number of cancers including pancreatic [22], breast [23,24], oesophageal [25], head and neck [26], prostate [27,28], and colorectal [29] cancers. Moreover, the chemotactic effect of CCR7 also has been found to be involved in the migration of leukemic cells to the CNS [30].…”
Section: Introductionmentioning
confidence: 99%